2012
DOI: 10.5051/jpis.2012.42.2.45
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of pain intensity of anterior middle superior alveolar injection with infiltration anesthetic technique in maxillary periodontal surgery

Abstract: PurposeThe aim of the present clinical trial was to compare pain during injection of anterior middle superior alveolar (AMSA) technique with that of infiltration injection technique in the maxilla in periodontal flap surgeries of patients referring to the Department of Periodontics, Faculty of Dentistry, Tabriz University of Medical Sciences.MethodsTwenty subjects with an age range of 20 to 40 years were selected for the present study. One side of the maxilla was randomly selected as the test side and the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…We confirmed the findings of Acharya et al [3] for the palatal aspect, but not for the buccal aspect, as injection was effective in 83.95% of PHT and 90.12% of PST sites around the molars. Shirmohammadi et al also used a conventional syringe for the injections and concluded that AMSA technique could be recommended for the anesthesia of palatal tissues in periodontal surgery [13].…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed the findings of Acharya et al [3] for the palatal aspect, but not for the buccal aspect, as injection was effective in 83.95% of PHT and 90.12% of PST sites around the molars. Shirmohammadi et al also used a conventional syringe for the injections and concluded that AMSA technique could be recommended for the anesthesia of palatal tissues in periodontal surgery [13].…”
Section: Discussionmentioning
confidence: 99%
“…Another split-mouth clinical trial reported no significant difference in pain during AMSA injections and local infiltrations for open-flap debridement. However, the postoperative pain was significantly less in the quadrant operated under anesthesia performed using the AMSA injection [19]. Another advantage of using AMSA injections for periodontal procedures is adequate hemostasis on the palate for harvesting soft-tissue grafts [1317], scaling and root planing (SRP) [16], open-flap debridement, and osseous surgery [17]; in contrast, conventional nerve blocks provide limited hemostasis only in the immediate areas surrounding the injection sites.…”
Section: Local Anesthesia For Periodontal Procedures In the Maxilla: mentioning
confidence: 99%
“…As already mentioned, certain local anesthetic (usually Lidocaine, Mepivacaine, or Articaine) during the AMSA anesthesia is injected into the lateral palate, that is, close to the 1st and 2nd premolars [1][2][3][4][6][7][8][9][10]13].…”
Section: Journal Of Orthodontics and Endodontics Issn 2469-2980mentioning
confidence: 99%
“…One of the procedures in dentistry is the AMSA (Anterior Middle Superior Alveolar) anesthesia, a relatively new local anesthetic technique, which has been introduced to achieve the pulpal anesthesia of the maxillary anterior teeth, and the surrounding tissues, by a single injection of certain anesthetic agent [1][2][3][4][5][6][7][8][9]. The local anesthetic, applied into the lateral palatal region at the level between the 1st and 2nd premolar, must diffuse all the way from the injection site to the anterior and middle part of the superior dental plexus, located just above the maxillary teeth roots, and to inhibit there the nociceptive neurotransmission along its dental (pulpal), and gingival and osseous twigs [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%